2011
DOI: 10.1002/cncr.26010
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of lung adenocarcinoma with KRAS mutations

Abstract: BACKGROUND: KRAS and epidermal growth factor receptor (EGFR) mutations are thought to play an important role in the carcinogenesis of lung adenocarcinoma. However, clinicopathological findings of KRAS mutated adenocarcinoma cases have not yet been fully clarified. The authors analyzed the relationship between the KRAS mutation and corresponding clinicopathological findings, focusing on nonmucinous and mucinous bronchioloalveolar elements. METHODS: EGFR and KRAS mutations were detected in DNA samples extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 46 publications
7
33
1
Order By: Relevance
“…Furthermore, KRAS mutations were often observed in conjunction with TP53 mutations in sarcomatoid carcinoma, which are invariably high grade, as opposed to the low-grade mucinous morphology that is classically associated with KRAS mutations alone. 28 Some of our KRASmutated tumors showed areas of typical mucinous adenocarcinoma, with abrupt transition to high-grade sarcomatoid areas; these relatively 'dedifferentiated' areas may correspond to the accumulation of additional genetic hits associated with tumor progression, including mutations in TP53. However, as the mutations in these morphologically distinct areas of the tumor were not investigated separately, this cannot be confirmed from our data.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, KRAS mutations were often observed in conjunction with TP53 mutations in sarcomatoid carcinoma, which are invariably high grade, as opposed to the low-grade mucinous morphology that is classically associated with KRAS mutations alone. 28 Some of our KRASmutated tumors showed areas of typical mucinous adenocarcinoma, with abrupt transition to high-grade sarcomatoid areas; these relatively 'dedifferentiated' areas may correspond to the accumulation of additional genetic hits associated with tumor progression, including mutations in TP53. However, as the mutations in these morphologically distinct areas of the tumor were not investigated separately, this cannot be confirmed from our data.…”
Section: Discussionmentioning
confidence: 82%
“…Wang et al (26) did not identify any significant differences in histological subtypes between the KRAS mutations and the wild-types; whereas, Yoshizawa et al (14) and Kakegawa et al (28) indicated that KRAS mutations were significantly associated with adenocarcinoma of mucinous tumor subtypes (P<0.001). Rekhtman et al (29) showed that KRAS mutations occurred more often in adenocarcinomas with a solid growth pattern (P=0.022).…”
Section: A B C D E Fmentioning
confidence: 98%
“…Notably, no patients with KRAS-mutated tumors with distant recurrence survived for >2 years after the recurrence, except 1 patient with pure invasive mucinous adenocarcinoma. It was demonstrated that KRAS-mutated adenocarcinomas may be divided into two groups according to lepidic histological growth pattern, with those patients without a lepidic component exhibiting a poor prognosis (17). In this study, 6 adenocarcinoma patients with no lepidic component were included, all of whom succumbed to the disease within 2 years of recurrence, whereas patients with tumors with a lepidic component also exhibited poor postrecurrence prognosis.…”
Section: Discussionmentioning
confidence: 93%
“…Genomic DNA was extracted from a 3-5 mm cube of tumor tissue using a DNA Mini kit (Qiagen, Hilden, Germany) and subsequently diluted to a concentration of 20 ng/µl. KRAS and EGFR mutations in lung cancer tissue were analyzed by peptide nucleic acid-enriched sequencing, as previously described (15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%